The use of Chromolaena odorata green manure to improve chemical properties of degraded Inceptisols and growth and yield of peanut - Hafifah, Hafifah; Nazirah, Laila; Nazaruddin, Muhammad (Journal of Degraded and Mining Lands Management, 2025)
Sustainable agriculture is a crucial solution to address land degradation and food security. This study examined the effects of Chromolaena odorata green manure and botanical pesticides on the chemical properties of degraded Inceptisols, which in turn affect the growth and yield of peanuts. The treatments tested were combinations of four dosages of Chromolaena odorata green manure (0, 10,000, 15,000, and 20,000 kg/ha), and three concentration levels of Chromolaena odorata botanical pesticide (0, 250, and 500 L/ha). Each polybag contained 10 kg of topsoil. The twelve treatments were arranged in a factorial randomized block design with three replications. The results showed that the application of Chromolaena odorata green manure at 20,000 kg/ha significantly improved soil pH, total nitrogen, and C/N ratio, which, in turn, increased leaf area, pod number, and fresh and dry pod weight of the plant. The application of botanical pesticide at 500 L/ha improved leaf area and reduced empty pods of the plant. The combination of green manure and botanical pesticides synergistically boosted soil fertility and peanut productivity. The application of (20,000 kg/ha green manure + 500 L/ha botanical pesticide) yielded the most significant improvements in soil organic C (54.28%), available P (65.11 ppm), and cation exchange capacity (13.10 cmol(+)/kg), along with plant growth and yield. These findings highlight the potential of Chromolaena odorata as an eco-friendly input for sustainable peanut cultivation.